Depressive Symptoms are Associated with low Serotonin Levels in Plasma but are not 5–HTTLPR Genotype Dependent in Older Adults - Trujillo Hernández, Pedro Enrique; Saenz Galindo, Aide; Saucedo Cárdenas, Odila; Villarreal Reyna, María de los Ángeles; Salinas Santander, Mauricio Andrés; Carrillo Cervantes, Ana Laura; Torres Obregón, Reyna; Esparza González, Sandra Cecilia (2021)
Depressive symptoms are diagnosed by physicians using scales but their pathophysiology is unclear. Low serotonin (5–HT) levels play an important role in depression, and the 5–HT transporter (5–HTT) is an important regulator of plasma serotonin levels and reuptake. Additionally, the 5–HTT gene-linked polymorphic region (5–HTTLPR) is associated with depression. The aim was to clarify the roles of plasma serotonin levels in plasma and the 5HTTPLR polymorphism in depressive symptoms in older adults. A total of 84 older adult participants were evaluated. Depressive symptomsweremeasuredusingtheCenterforEpidemiologicStudiesDepressionScaleof20items(CESD–20).Theplasma serotonin levels were determined by ELISA, and the 5–HTTLPR genotype was analyzed by PCR. Depressive symptoms were present in 39.3% (N = 33) of the participants. The median plasma serotonin level was 204.34 ng/mL (SD = 93.88). A significant correlation was found between the CESD–20 scale and plasma serotonin levels (r =–.256; p = .019). Low serotonin levelswereassociatedwiththepresenceofdepressivesymptoms(p=.001).The5–HTTLPRanalysisshowedthat of the 84 older adults, 35.7% had the SS genotype, 10.7% had the LL genotype, and 53.6% were heterozygous. The 5HTTLPRpolymorphism wasnotassociated with depressive symptoms (p = .587) and plasma serotonin levels (p = 0.391). Depressive symptoms correlate with low serotonin levels in plasma, but not with the 5–HTTLPR polymorphism in older Mexican adults.